Analisis Kadar Amonia dan pH pada Limbah Cair Kanal 32 (K-32) PT Pusri Palembang - Rahman, Fachtur (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2019)
ABSTRACT Industrial liquid waste PT Pupuk Sriwidjaja (Pusri) Palembang, contain Nitrogen compounds, in the form of ammonia. The liquid waste is derived from a small canal – canal flows from the unit, the unit of urea and ammonia unit utilities, before being processed to be discarded into the Musi River. One of the canals that connected on 3 of these units and empties into the Musi River is a canal 32, also known as K-32. This research aims to know the implementation of the control of environmental pollution, by analyzing the water quality of waste based on the levels of ammonia and pH. The methods used in the research is qualitative and quantitative methods, by looking at the color change in the sample which has reacted with reagent Nessler, and using UV-Vis Spectrophotometer instrument in order to find out the levels of ammonia on liquid waste. Based on the results of the study, the average pH obtained on channel 32 (K-32) is 8.52, while average levels of ammonia was 58.92 ppm (0.05 in kg/tons). All of the result were in quality standard based on Ministry regulation no. 5 which issued in 2014. Keywords : Ammonia; Liquid Waste; pH; Reagent Nessler; Spektrofotometer UV-Vis